LITERATURE STUDY: THE IMPACT OF SOCIAL MEDIA ON THE BEHAVIOR OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Fatmawati; Yusrizal (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research analyzes the impact of social media use on the behavior of fourth grade elementary school students. This research is qualitative research with a Systematic Literature Review (SLR) approach. This research collects secondary data from various journals and related literature. The research results show that social media has both positive and negative impacts on student behavior. Positive impacts include ease of access to information, increased creativity, and support for social interaction and learning. However, negative impacts such as impaired concentration, decreased quality of direct interactions, potential for cyberbullying, and exposure to inappropriate content were also found. In an educational context, collaboration between teachers and parents is very important to direct the use of social media wisely, in order to minimize the negative impacts and maximize the benefits. This research recommends the need for intensive supervision and digital education for elementary school students to encourage positive and responsible use of social media.